PESANTREN DI TENGAH GEMPURAN SEKOLAH MODERN - Muh Subhan Ashari (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2019)
This article wants to explain the history of the appearing and the growing of “pesantren” school, and to explain the secrets behind the solidity of pesantren to face of modern school. “Pesantren” is the first educational institution in Indonesia which it adopted the Hindu-Buddhist education system from India, and adopted the “mosque” education system from Islam. There are at least five basic elements in the pesantren education system which are mosques, kyai, santri, dormitories, and yellow books. The “pesantren” education system was able to survive in the midst of the modern education system, because in reality pesantren are always active in making changes to adapt the conditions of their times. This can be seen by the emergence of at least two types of “pesantren”, namely “salaf” (traditional pesantren) and “khalaf” (modern pesantren). The education system in the “salaf pesantren” is still very strong in maintaining its traditions such as yellow book,